Supplementation with DDGS in grazing steers and its effect on productive performance and ultrasonographic measurements - Aguilar-Alfaro, Keylor (2023)
The effect of supplementation with distillers dried grains with corn solubles (DDGS) in castrated Brahman steers in a grazing system on productive performance variables and ultrasonographic measurements was evaluated. The study was carried out in a rotational grazing system in the humid tropics of Costa Rica, where the animals were supplemented for 110 days of finishing and underwent two nutritional supplements or treatments with 16 repetitions each, the first corresponded to a supplement for commercial use in the country and the second based on DDGS. The animals were weighted monthly to calculate average daily gain (ADG) and body condition score (BCS) was measured at the beginning and at the end of the fattening period. Ultrasonographic measurements of muscle depth, back fat thickness, rump fat thickness, and marbling were evaluated. No significant differences were obtained between the treatments (p > 0.05) for any of the variables. Still, the ADG values (0.98 kg for T1 and 0.99 kg for T2) are indicative of a good productive performance under the conditions of this study and higher than those regularly reported for Bos indicus animals (0.70-0.80 kg). Regarding the final BCS of the animals (6.91 for T1 and 6.81 for T2), the values obtained are a sign of good productive performance under these states. They are considered acceptable for Bos indicus animals in tropical conditions (CC 6-7). On the other hand, the measurements obtained are considered within the expected ranges for Bos indicus animals in tropical conditions. It was possible to conclude that supplementation with DDGS in grazing Brahman steers did not have effects equivalent to a commercial concentrate on productive performance and ultrasonographic measurements under the conditions of this study.